Final destination 2 [videorecording (DVD)] - Larter, Ali, 1976-; Cook, A. J., 1978-; Landes, Michael; Carson, T. C., 1958-; Tracy, Keegan Connor, 1971-; Carter, Sarah, 1980-; Boyd, Lynda, 1965-; Todd, Tony, 1952- (Infinifilm., 2003)
Clear Rivers, the only surviving passenger of the ill-fated Flight 180, is certain Death will claim her. Kim, who has begun to display precognitive powers, is driving along the highway when she has a vision involving a terrible highway accident. Moments later the accident occurs, but Kim has saved herself and seven others from death. She inadvertently has put a rift in Death's design. Now Death will track down the souls he meant to take that day. Clear and Kim must now work together to stop Death from taking the lives of those she saved.